Protective effect of hydroxytyrosol against hyperglycemia-induced phosphatidylserine exposure in human erythrocytes: focus on dysregulation of calcium homeostasis and redox balance - Rosaria Notariale; Claudia Moriello; Nicola Alessio; Vitale Del Vecchio; Luigi Mele; Pasquale Perrone; Caterina Manna (Redox Biology, 2025)
Diabetes is a widespread chronic disease that poses serious health concerns due to its numerous associated complications, including an increased risk of cardiovascular diseases. Under conditions of prolonged hyperglycemia, erythrocytes (RBC) undergo the breakdown of the natural phospholipid asymmetry, triggered by cell surface exposure of phosphatidylserine (PS) associated with increased prothrombotic activity. The aim of the present study was to provide insights into the potential molecular mechanisms underlying, focusing on two phospholipid translocases, ATP-dependent flippase ATP11C and calcium-dependent scramblase PLSCR1. The possible protective effect exerted by the hydroxytyrosol (HT), a powerful phenolic antioxidant present in olive oil, was also tested. Exposure of intact human RBC to high glucose (25–50 mM) results in a dose-dependent increase in PS-exposing RBC, which can be prevented by HT at concentrations as low as 5 μM. Furthermore, our study reveals that PLSCR1 activity is significantly higher under hyperglycemic conditions. In line with this finding, immunocytochemical analysis indicates increased membrane expression of this enzyme. Both alterations can be prevented by HT pre-treatment. Conversely, no variation in ATP11C is observable. Importantly, intracellular calcium measurement reveals a significant rise, suggesting that dysregulation of calcium homeostasis may be a key mechanism underlying both the change in scramblase activity as well as the HT protective effect observed. In this case too, in fact, HT exhibits a protective effect. Accordingly, when cells are exposed to high glucose in a calcium-free medium no variation is observable. Finally, we report that HT is able to prevent glucose-induced alteration in redox balance by reducing ROS formation and the decline in intracellular glutathione, likely due to its high scavenging potential as well as to the proposed recycling process cycle that could regenerate reduced glutathione from its radical. All together our findings point to RBC as an additional target in the management of the cardiovascular complications associated with diabetes and indicate HT as nutritional/nutraceutical strategy for their prevention in diabetic patients.